Implementation of multiphase piezoelectric composites energy harvester on aircraft wingbox structure with fuel saving evaluation. (15th October 2018) - Akbar, M.; Curiel-Sosa, J.L.
Abstract: The multiphase composite with active structural fiber (ASF) has proven able to provide better optimization between actuating and load bearing capability compared to a pure piezoelectric material. In this paper, the multiphase composite application is further extended for energy harvesting purpose. The Double-Inclusion model combined with Mori-Tanaka method is implemented in a computational code to estimate the effective electro-elastic properties of the multiphase composite. The effective composite properties obtained via the present code are in good agreement with the analytical, experimental and finite element results. The multiphase composite with different composition is applied to a typical jet aircraft wingbox with 14.5 m halfspan. The energy harvesting evaluation by means of hybrid FEM/analytical piezoelectric energy harvester model is presented. A new procedure to investigate the trade-off between the aircraft weight, the fuel saving and the energy harvested is developed. The results pointed out that the equivalent fuel saved from the power generated by the wingbox is more than enough for 1 h Auxiliary Power Unit (APU) operation.